Plasma concentratıon-tıme profıle of a sıngle dose of enterıc-coated omeprazole ın male and female healthy volunteers - İskender, Ece; Aslan, Neslihan; Gören, M. Zafer; Tellioğlu, Tahir; Akın, Serap; Erin, Nuray; Aker, Rezzan; Onat, Filiz; Berkman, Kemal; Oktay, Şule (My University, 2000)
Objective: The bioavailability of a single dose (20 mg) of two enteric-coated omeprazole formulations, marketed in Turkey, given 10-15 min before breakfast, was studied in 12 healthy volunteers (6 males and 6 females) in a doubleblind, crossover design. Methods: Blood samples were collected prior to and at 10 time points within 12 hrs. after dosing. Plasma omeprazole concentrations were measured by HPLC technique in our laboratory. Results and Conclusions: The two products were found to be bioequivalent in terms of extent of absorption (the area under the plasma concentration-time curves). Multipeak plasma concentration profiles were seen in most of the subjects with both products. Time to the earlier peaks was 1-2 hrs. and those peaks were lower in amplitude than the peaks reached approximately 4.5 hrs. after the application. Interestingly, the multipeak profile was more frequent and the earlier peaks were significantly higher in female subjects than in males. The reason for this gender difference in multipeak plasma concentration - time profile of oral omeprazole needs further investigation.
Keywords: Omeprazole - Bioavailability - Enteric - coated capsules - Gender difference